The Influence of Operational Risk and Supply Chain Risk Management on Operational Performance - Lamhot Lamhot; Yolanda Masnita Siagian (Universitas KH. Abdul Chalim Mojokerto, 2025)
The reliability of company management in handling operational risks including managing extra capacity, alternative transportation modes, and contingency plans support on-time delivery. Management awareness of the impact of the global economic downturn and external legal issues strengthens the company's operations, including the stability of supply chain technology. Good communication and customer involvement in the Just in Time (JIT) system and adequate maintenance maintain product quality and safety. High supplier and production operator involvement increases responsibility and productivity. This study uses primary data from questionnaires distributed to 251 employees in the logistics and related industries in Indonesia, with a purposive sampling method and Structural Equation Modeling analysis. The study's results indicate the influence of Supply Risk, External Risk, and Demand Risk on Operational Risk and the impact of Operational Risk and Supply Chain Risk Management on Operational Performance.